Connecting theories in mathematics education: from bricolage to professionalism - Wedege, Tine (NOMAD Nordic Studies in Mathematics Education, 2010)
Connecting theories is a normal activity in the practice of mathematics education researchers and the theories come from within the field of mathematics education (”home-brewed” theories) or from outside (psychological, sociological, anthropological; philosophical, linguistic etc. theories). Thus, the researcher needs methods and strategies for connecting theories; e.g. comparing/contrasting and integrating/ synthesizing. I argue that a meta-language is also needed in order to move from bricolage to professionalism in the work of theory connection. Drawing on Radford’s morphology of theories as triplets of principles, methodologies and research questions, I suggest a set of quality criteria for research papers and reports which focuses on the explicitness in reporting theory connection.